Surgical Management of Pulmonary Mucormycosis in Third-Trimester Pregnancy - Ramirez, Joel L.; Urisman, Anatoly; Kukreja, Jasleen; Kratz, Johannes R. (The Thoracic and Cardiovascular Surgeon Reports, 2018)
Background Pulmonary mucormycosis is a rare fungal infection that carries a high mortality. Given the rarity of this disease, its management has not been well established.Case Description We report a 36-year-old female presenting with right middle and lower lobe pulmonary mucormycosis during the third trimester of pregnancy. Diagnosis was established using chest computed tomography followed by bronchoalveolar lavage and lung biopsy. Prompt initiation of amphotericin B and right middle and lower lobe lobectomy resulted in maternal survival and fetal viability.Conclusion This favorable outcome is attributed to extensive communication between treatment teams in addition to comprehensive surgical planning.
Keywords: pregnancy; mucormycosis; pulmonary mucromycosis